Pengetahuan dan Rasionalitas Pasien Terhadap Pengobatan Sendiri di Apotek - Aulia Rahmi, Ika (Politeknik Tiara Bunda, 2021)
knowledge about self-medication. This sampling was carried out using the Purposive Sampling method, namely a sampling determination technique based on certain considerations. Data collection took place for two months using a questionnaire instrument as data collection for 90 respondents. Through the primary data obtained in the form of questions distributed to respondents who came to buy medicine at the Pharmacy. The data obtained by collecting the answers to the questionnaire were then tabulated, scored, and presented. Based on the results of the study, it was concluded that the level of public knowledge about self-medication in three Pharmacies, which stated that they knew 77.19%, did not know 14.67%, and did not know 8.12%. So it was concluded that the level of public knowledge about self-medication was included in the high category, namely 77.19%